Bio-efficacy of herbicide combinations for control of weeds in transplanted rice (Oryza sativa) - BHATT, P SPANDANA; YAKADRI, M; MADHAVI, M; SRIDEVI, S; RANI, P LEELA (The Indian Journal of Agricultural Sciences, 2020)
The present study during kharif 2013-14 at Professor Jayashankar State Agricultural University, Hyderabad, Telangana to study the efficiency of herbicide combinations for controlling weeds in rice. The study comprised 14 treatments in Randomized block design replicated thrice. During both years of investigation the higher weed control efficiency and herbicide efficiency index was noticed with hand weeding twice at 25 and 45 DAT, pyrazosulfuron ethyl 20 g/ha as PE at 3 DAT followed by manual weeding at 25 DAT and pretilachlor 750 g/ha as PE at 3 DAT followed by metsulfuron methyl + chlorimuron ethyl 4 g/ha as PoE at 25 DAT. Significantly higher grain yield and gross returns were noticed with hand weeding twice at 25 and 45 DAT and was comparable with pyrazosulfuron ethyl 20 g/ha as PE at 3 DAT followed by manual weeding at 25 DAT, pretilachlor 750 g/ha as PE at 3 DAT followed metsulfuron methyl + chlorimuron ethyl 4 g/ha as PoE at 25 DAT and bispyribac sodium 20 g/ha + metsulfuron methyl + chlorimuron ethyl 4 g/ha as PoE at 25 DAT. However, pyrazosulfuron ethyl 20 g/ha as pre emergence at 3 DAT followed by manual weeding at 25 DAT noticed higher net returns and B:C ratio.